'If you take a horse to water it usually does drink'—mandatory mediation of trust disputes in New Zealand: Wright v Pitfield [2022] NZHC 385. Issue 8 (10th August 2022) - Barber, Simon
Abstract: Under the Trusts Act 2019, New Zealand's High Court can compel parties to attend mediation against their will. Some argue that this compulsion is anathema to the voluntary and consensual nature of mediation. Others argue that it is pragmatic—recognising the proven success of mediation and its myriad advantages over litigation. In Wright v Pitfield, a typical family trust dispute between former spouses, the High Court exercised this power for the first time—finding that it was the 'type of case Parliament had in mind when providing jurisdiction for the Court to require parties to attend mediation'. The question is whether courts will take a similarly liberal approach in more exceptional cases.